Short-term Labour Market Effects of COVID-19 and the Associated National Lockdown in Australia: Evidence from Longitudinal Labour Force Survey - Cahit Guven; Panagiotis Sotirakopoulos; Aydogan Ulker (Global Labor Organization (GLO), 2020)
We examine the short-term labour market effects of COVID-19 and the associated national lockdown in Australia by estimating person-fixed-effects models using the Longitudinal Labour Force Survey. COVID-19 decreased labour force participation (LFP) by 2.1%, increased unemployment by 1.1% and reduced weekly working hours by 1.1. The national lockdown decreased LFP by 3.3%, increased unemployment by 1.7%, and decreased weekly working hours by 2.5. The probability of working on Fridays decreased by 10% while working fewer hours due to being on leave, work shifts, not having enough work and losing jobs all increased due to the lockdown. The pandemic and the lockdown increased underemployment and job search efforts significantly. In terms of heterogeneity of these effects, our analysis shows that those with up to high-school education experienced larger reductions in their LFP and working hours than others. However, immigrants and individuals with shorter job tenure or occupations unsuitable for remote work were hit the hardest in terms of unemployment.
Keywords: I15; I18; J21; 330; COVID-19; National Lockdown; Labour Market; Short-term; Australia